Systematic review of literature on sustainable roof-tiles for product development - Janilce dos Santos Messias Negrão; Rafaela Ribas Rocha; Adriana de Paula Lacerda Santos; Marcell Mariano Corrêa Maceno; Thaisa Lana Pilz (The Journal of Engineering and Exact Sciences)
This article is based on the Product Development Process (PDP), with the study of alternative materials, both solid waste and possible composites, for tile production. The aim of this research was to performed a Systematic Review of Literature in order to find a low cost, durable and ecologically interesting solution for use in popular dwellings. The research method used was the search for articles, making a systematic review allied to a bibliometric analysis. Four electronic databases were accessed and articles in Portuguese and English were selected to collect important information using the 5W2H tool. Also, a general survey was carried out on prices and weights of tiles in the market. The compilation of data provided sufficient material for proposal development, which was mainly based on the use of Tetra-Pak® packaging for the development of tiles PET bottles also had a strong potential of use, since they are lightweight and ecologically sustainable. On the other hand, the price was still high when compared to what is on the market. Alternatively, tiles produced with Tetra-Pak® packaging were the most appropriate tiles for projects due to their quality, low cost and efficiency for use in popular houses, also presenting environmental benefits.